A revised 1000 year atmospheric δ13C‐CO2 record from Law Dome and South Pole, Antarctica. Issue 15 (15th August 2013) - Rubino, M.; Etheridge, D. M.; Trudinger, C. M.; Allison, C. E.; Battle, M. O.; Langenfelds, R. L.; Steele, L. P.; Curran, M.; Bender, M.; White, J. W. C.; Jenk, T. M.; Blunier, T.; et al.
Abstract : [1] We present new measurements of δ 13 C of CO2 extracted from a high‐resolution ice core from Law Dome (East Antarctica), together with firn measurements performed at Law Dome and South Pole, covering the last 150 years. Our analysis is motivated by the need to better understand the role and feedback of the carbon (C) cycle in climate change, by advances in measurement methods, and by apparent anomalies when comparing ice core and firn air δ 13 C records from Law Dome and South Pole. We demonstrate improved consistency between Law Dome ice, South Pole firn, and the Cape Grim (Tasmania) atmospheric δ 13 C data, providing evidence that our new record reliably extends direct atmospheric measurements back in time. We also show a revised version of early δ 13 C measurements covering the last 1000 years, with a mean preindustrial level of −6.50‰. Finally, we use a Kalman Filter Double Deconvolution to infer net natural CO2 fluxes between atmosphere, ocean, and land, which cause small δ 13 C deviations from the predominant anthropogenically induced δ 13 C decrease. The main features found from the previous δ 13 C record are confirmed, including the ocean as the dominant cause for the 1940 A.D. CO2 leveling. Our new record provides a solid basis for future investigation of the causes of decadal to centennial variations of the preindustrial atmospheric CO2 concentration. Those causes are of potential significance for predicting future CO2 levels and when attempting atmospheric verification of recent and future global carbon emission mitigation measures through Coupled Climate Carbon Cycle Models. Key Points: New and revised, firn and ice δ 13 C‐CO2 measurements from Antarctica Improve consistency between ice and firn δ 13 C‐CO2 measurements Net natural CO2 fluxes between atmosphere, ocean and land inferred